Documentary Sources for Art History in the Territories of the Military Orders: the Juzgado de Iglesias (1695-1836) - García del Real Marco, Berta (Cuadernos de Historia Moderna, 2018)
The Juzgado de Iglesias is an institution created in 1695 with the purpose of ensuring the good conservation and decoration of the churches located in the territories of the Orders of Santiago, Calatrava and Alcántara, whose maintenance was a duty of the Council of the Military Orders. From 1695 until its suppression by Royal Decree of July 30, 1836, it produced a considerable amount of documents providing a wealth of information on more than 300 parish churches located in the current territories of Castilla-La Mancha, Extremadura and Andalusia. The documentary fond, preserved in the Archivo Histórico Nacional, is now in the process of organization. It includes inventories of jewelry, books and objects of worship, architectural projects for the repair and reconstruction of buildings, new altarpieces, confessionals, organs, etc. These documents constitute a valuable source of information for the study of Baroque and Neoclassical art in the area that may enable to enrich our knowledge of the subject.
Keywords: Military Orders; Council of the Military Orders; Parrish churches; Religious Architecture; Baroque Art; Neoclassical Art; Documentary sources.